Challenges of female entrepreneurship: Empowerment and resilience on the Tijuana border - Galván Vela, Esthela; Sorzano-Rodríguez, Deisy Milena; Parra Elizalde, Karina (UMA Editorial. Universidad de Málaga, 2025)
The pursuit of gender equality is not only a matter of social justice but also a crucial factor for sustainable development. Gender inequalities hinder economic growth and limit communities' ability to effectively address global challenges such as poverty and lack of access to education. In this context, female empowerment serves as a response to the need for women to develop resilience skills, challenging the traditional narrative that positions women as the center of vulnerability and inaction in adverse situations. An ideal scenario for identifyingthe impact of women on society and the economy is the analysis of the challenges and opportunities faced by female entrepreneurs in Tijuana, Mexico. This perspective critically examines their efforts to embrace their gender roles and achieve the long-desired equity and empowerment. Therefore, the objective of this research was to analyze the challenges and opportunities that entrepreneurs face on the Tijuana border, assessing how their experiences contribute to female empowerment and resilience in a complex socioeconomic context. Through a critical approach, the study aimed to identify structural barriers that limit the development of their ventures and propose public policies to help them overcome these obstacles. To achieve this objective, a qualitative study was conducted using data collection techniques that included 23 interviews and four focus groups. Grounded Theory methodology was employed under a constant comparative method. The analysis resulted in a considerable array of categories and codes, highlighting issues such as gender discrimination, questioning of leadership and managerial skills, exclusion from financial decision-making, lack of recognition, the role of women in the household—including implicit limitations of domestic and caregiving work—violence, and harassment. Among the main sources of empowerment identified were familial support in achieving a balance between time and responsibilities associated with their roles as women, the initiative and desire to gain training in business management, and the efforts of associations and organizations to provide training and raise awareness. The study concludes that female entrepreneurship in Tijuana faces limitations stemming from a traditional view of gender roles, where women are seen primarily ascaregivers responsible for household duties. A series of public policies are proposed to recognize and highlight the pivotal role of women in resource management and the promotion of innovative solutions.
Pág. 30
Keywords: Female Entrepreneurship; Empowerment; Resilience; Entrepreneurship Challenges; Female Entrepreneurship Ecosystem; Campus Tijuana